2009
DOI: 10.17221/10/2009-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fine root traits between Norway spruce (Picea abies [L.] Karst.) and European beech (Fagus sylvatica L.) - A case study in the Kysucké Beskydy Mts

Abstract: Interspecific comparisons of the fine root "behaviour" under stressful situations may answer questions related to resistance to changing environmental conditions in the particular tree species. Our study was focused on Norway spruce (Picea abies [L.] Karst.) and European beech (Fagus sylvatica L.) grown in an acidic soil where acidity was caused by past air pollution in the Kysucké Beskydy Mts., North-Western Slovakia. Between April and October 2006, the following fine root traits were studied: biomass and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…one vegetation period) or not of required level of detail were not considered (e.g. Konôpka et al 2005;Konôpka 2009;López et al 2001). At least two measurements from the same month in two consecutive years are the minimum requirement for the calculation of root production.…”
Section: Calculations Of Fine-root Productionmentioning
confidence: 99%
“…one vegetation period) or not of required level of detail were not considered (e.g. Konôpka et al 2005;Konôpka 2009;López et al 2001). At least two measurements from the same month in two consecutive years are the minimum requirement for the calculation of root production.…”
Section: Calculations Of Fine-root Productionmentioning
confidence: 99%
“…Similarly, two studies which manipulated rainfall by roof exclusion measured higher fine root mortality and necromass under low water availability while fine root biomass was generally higher under normal precipitation (control) (Konôpka et al 2007 ; Persson et al 1995 ). Studies utilizing increasing aridity along time series also found a general trend of higher necromass with drier environments (Eissenstat et al 2000 ; Konôpka 2009 ; Konôpka & Lukac 2013 ; Makkonen & Helmisaari 1998 ; Montagnoli et al 2019 ), and support for this trend also comes from studies along precipitation gradients (Fuchs et al 2020 ; Meier & Leuschner 2008 ). Interestingly, Picea abies increased root suberization under drought conditions indicating a ‘slow’ ecological strategy, while Fagus sylvatica increased the production of thin, ephemeral, absorptive fine roots during drought indicating a ‘fast’ strategy (Nikolova et al 2020 ).…”
Section: Discussionmentioning
confidence: 91%